Nile tilapia (oreochromis niloticus) protein hydrolysate with antioxidative and nitric oxide inhibitory activities - Sureeporn Kangsanant (Prince of Songkla University, 2015)
Thesis (Ph.D. (Functional Food and Nutrition)--Prince of Songkla University, 2014